Sports biomechanical information acquisition and evaluation for kayaking events - Zuchang, M.; Jingmin, Z.; Yining, S.; Tao, M. (International Journal of Information Acquisition, 2009)
Intensive understanding of sports biomechanical principles is an essential issue for sprint kayaking. In recent years, the authors have studied the acquisition of biomechanical information and the evaluation of competitive ability on sprint kayaking. In this study, first, an oar force sensor was developed to detect the stroke forces applied by paddler. The sensor was attached to a paddle with minimum mechanical involvement, hence the mechanical properties of the paddle was not changed. Second, an on-water instrument of biomechanical information acquisition was developed to detect stroke force, stroke frequency, stroke power, kayak speed, and acceleration synchronously. Third, 12 evaluation factors for kayaking ability were proposed based on the factor analysis. The 12 factors include (1) the stroke rate; (2) the speed fluctuation; (3 and 4) the hull pose (L/R); (5 and 6) the stroke force (L/R); (7 and 8) the endurance (L/R); (9 and 10) the stroke technique (L/R); (11 and 12) and the stroke rhythm (L/R). Finally, the stroke rate and the forward stoke technique was analyzed briefly.